Identification and Function Analysis of enolase Gene NlEno1 from Nilaparvata lugens (Stål) (Hemiptera:Delphacidae). Issue 1 (6th June 2015) - Wang, Wei-Xia; Li, Kai-Long; Chen, Yang; Lai, Feng-Xiang; Fu, Qiang
Abstract : The enolase [EC 4.2.1.11] is an essential enzyme in the glycolytic pathway catalyzing the conversion of 2-phosphoglycerate (2-PGE) to phosphoenolpyruvate (PEP). In this study, a full-length cDNA encoding α-enolase was cloned from rice brown planthopper ( Nilaparvata lugens ) and is provisionally designated as NlEno1 . The cDNA sequence of NlEno1 was 1, 851 bp with an open reading frame (ORF) of 1, 305 bp and encoding 434 amino acids. The deduced protein shares high identity of 80–87% with ENO1-like protein from Hemiptera, Diptera, and Lepidoptera speices. The NlEno1 showed the highest mRNA expression level in hemolymph, followed by fat body, salivary gland, ovaries and egg, and showed trace mRNA levels in testis. The mRNA of NlEno1 showed up-regulated level in virulent N. lugens population Mudgo, IR56 and IR42 when compared with TN1 population. Injection of double-stranded RNA (dsRNA) of NlEno1 into the adults significantly down-regulated the NlEno1 mRNA level along with decreased eggs and offspring. Moreover, injection of NlEno1 -dsRNA decreased mRNA level of Vitellogenin ( Vg ) gene. These results showed that the NlEno1, as a key glycolytic enzyme, may play roles in regulation of fecundity and adaptation of N. lugens to resistant rice varieties.